Barriers and enablers of early health-seeking behaviour among women with preeclampsia and eclampsia: a qualitative study at a National referral hospital in Uganda - Geofrey Muhindo; Patience Muwanguzi; Shirley Moore; Mark Kaddumukasa; Martha Sajatovic; Scovia Nalugo Mbalinda (BMC Pregnancy and Childbirth)
Abstract Background Globally, 2–8% of women experience hypertensive disorders in pregnancy (HDPs), including preeclampsia and eclampsia, which are the second leading cause of maternal mortality and morbidity. According to the management protocol for preeclampsia in Uganda, weekly follow-up is recommended for women with preeclampsia without severe features who are below 37weeks of gestation; however, this has not been feasible to most cases of preeclampsia/eclampsia (PE/E). There is still limited information describing barriers and enablers of early health-seeking behaviour amongst women with PE/E, yet this is needed to improve their healthcare. This study explored the barriers and enablers of early health-seeking behaviour among women with PE/E. Methods We employed an exploratory descriptive qualitative design, involving 18 participants previously diagnosed with PE/E during antenatal, intrapartum, or postnatal periods, sampled using maximum variation sampling. This involved searching for a variation in the special aspects of the study population, including age, condition/diagnosis of either preeclampsia or eclampsia and the timing of diagnosis. Data were collected using a semi-structured interview guide from July to August 2023 and analysed manually through inductive content analysis. Results The interviews revealed three main themes as barriers: individual barriers; structural and logistical and socio-cultural barriers. Limited knowledge and awareness about PE/E, financial constraints, drug stockouts, beliefs and misconceptions were reported to be key barriers to early health-seeking behaviour. Social support, perceived good health care services and compliance with medical advice emerged as enablers. Conclusion This research implicates healthcare workers, including doctors and midwives, to create awareness and teaching about hypertensive disorders in pregnancy among the community through packaging relevant educational messages and sessions. This can be during antenatal contacts, community sensitisation outreaches and over media platforms like TV and FM radio stations. Furthermore, care for pregnant women should be more client-centred and flexible to allow the drop-in clients, especially those with complications in pregnancy, to enhance timely diagnosis and better health service delivery. Our study further highlights the social need for partners, family members, friends and other community members to support women with preeclampsia, accept and consider them like any other client/patient.